2021
DOI: 10.1016/j.jemermed.2021.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Retinal Detachments in a Healthy 22-year-old Woman After Moderna SARS-COV-2 Vaccination

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
0
12
0
1
Order By: Relevance
“…As a follow up to this, two recent case reports published in the USA reveal a possible association with mRNA vaccines and damage to the retina. Subramony et al [22], for example, reported a case of bi-lateral retinal detachment in a healthy 22-year-old after vaccination with the Moderna mRNA vaccine. This individual had no health issues, but upon ophthalmologic exam, was determined to have lattice degeneration.…”
Section: Lipid Nanoparticles (Lnps) In the Covid-19 Mrna Vaccinesmentioning
confidence: 99%
“…As a follow up to this, two recent case reports published in the USA reveal a possible association with mRNA vaccines and damage to the retina. Subramony et al [22], for example, reported a case of bi-lateral retinal detachment in a healthy 22-year-old after vaccination with the Moderna mRNA vaccine. This individual had no health issues, but upon ophthalmologic exam, was determined to have lattice degeneration.…”
Section: Lipid Nanoparticles (Lnps) In the Covid-19 Mrna Vaccinesmentioning
confidence: 99%
“…Starting from an analysis of the literature on eye complications of COVID-19 vaccines, it is evident that nevertheless trillions of vaccine administrations ocular side effects generally are very rare, less than one hundred severe ophthalmological side effects are described in normal population in the last three years either in registration trials or in literature. [8][9][10][11][12] Main ocular complication are inflammatory manifestations both in anterior or posterior segment, and ocular thrombosis or ischemic manifestations, [13][14][15][16][17] occurred in strict time relation, one to three days, with vaccine shot release. [23][24][25][26][27][28][29][30][31][32] But no reports are present on the occurrence of side effects in patients affected by rare ophthalmological disease.…”
Section: Discussionmentioning
confidence: 99%
“…All 4 reported cases were in females, which is in conjunction with findings by [ 204 ] fuelling the possibility of further clinical analysis regarding any relationship between sex and occurrence of hypersensitivity reactions after administration of the mRNA-1273 vaccine. A 22 years old myopic female in the USA experienced bilateral retinal detachment after vaccination with mRNA-1273 [ 210 ]. In July 2021, EMA confirmed myocarditis and pericarditis as side effects of mRNA-1273 [ 211 ].…”
Section: Vaccines Approved For Public Usementioning
confidence: 99%